Interactive Communication Strategies to Support the Implementation of Multidimensional Literacy and Language Education in Inclusive Settings for Achieving Sustainable Development Goals (SDGs) - Amalia, Eva; Purwanta, Edi; Purbani, Widyastuti; Kharisma, Nanda Veruna Enun; Mufidah, Zulfin Rachma (International Journal of Language Education, 2025)
This study aimed to investigate how interactive communication strategies facilitate the implementation of multidimensional literacy (encompassing linguistic, cognitive, sociocultural, and developmental aspects) in inclusive classrooms, with a particular emphasis on language education and the achievement of Sustainable Development Goals (SDGs) (i.e., Quality Education). A qualitative case study was conducted in an inclusive elementary school in Yogyakarta, Indonesia. Data were collected through participatory observation, semi-structured interviews with teachers and students, and document analysis. Findings show that teachers applied adaptive strategies such as open-ended questions, paraphrasing, positive feedback, visual cues, and choice-based questioning, enabling both regular and special needs students to participate actively. These strategies enhanced sentence construction, reading comprehension, sociocultural awareness, and self-confidence by fostering meaningful dialogue and adaptive scaffolding. The study highlights that interactive communication is not merely supportive but central to equitable, holistic literacy and language education in inclusive contexts, contributing to inclusive and transformative education practices aligned with SDGs.